THE BASIC DIRECTIONS OF CARDIAC REHABILITATION OF PATIENTS WITH CARDIAC DISEASES - Vlasenko, O.A.; Vlasenko, M.A.; Bruev, N.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The methodical and clinical aspects of restoration treatment, necessity of approaches of the systems, are considered to treatment of patients various pathology. In this article is proved (founded) the importance of medicine therapy like the one of the elements of recovery treatment.